How local stakeholders perceive agroforestry systems: an Italian perspective - Camilli, Francesca; Pisanelli, Andrea; Seddaiu, Giovanna; Franca, Antonello; Bondesan, Valerio; Rosati, Adolfo; Moreno, Gerardo; Pantera, Anastasia; Hermansen, John E.; Burgess, Paul J. (Springer, 2017)
This paper reports the results of a study conducted in Italy, within the AGFORWARD (2014–2017) project, aimed at promoting innovative agroforestry practices in Europe. Agroforestry offers a means for maintaining food production whilst addressing some of the negative environmental effects of intensive agriculture. This study aims to elicit the positive and negative points of view and perceptions of local stakeholders in Italy in relation to three types of agroforestry systems. The Participatory Research and Network Development was implemented in three workshops conducted in Sardinia, Umbria, and Veneto regions, and applied adopting a common methodological protocol. Qualitative data were obtained using open discussions with stakeholders on key issues, challenges and innovations. Quantitative data were obtained from stakeholders completing questionnaires during the workshops. A statistical analysis was applied to elicit the differences in stakeholders’ positive and negative perceptions in relation to production, management, environment and socio-economy aspects. Although the participants in the study came from different geographical and socioeconomic contexts with varied educational and cultural backgrounds, the different professional groups (farmers, policy-makers and researchers) and the three workshops generally shared similar perceptions of the benefits and constraints. The effects of agroforestry on production and the environment were generally perceived as positive, whilst those related to management were generally negative. The process of bringing the groups together seemed to be an effective means for identifying the key research gaps that need to be addressed in order to promote the uptake and maintenance of agroforestry.
Keywords: Agroforestry; EU policy; Innovation; Landscape; Ecosystem services